let-7g-5p suppresses the proliferation and expansion of hepatic stellate cells in liver fibrosis via targeting FGF5 - Zhou, Jiaming; Huang, Siyan; Yang, Yidan; Cong, Yutong; Chen, Yuwen; Ding, Youyou; Lu, Mengwen; Li, Meiyuan (Penerbit Universiti Kebangsaan Malaysia, 2025)
Hepatic stellate cells (HSCs) and their activated phenotype (activated HSCs, aHSCs) function as crucial effector cells in the onset of liver fibrosis. In recent years, microRNAs (miRNAs) have emerged as a promising therapeutic approach for diseases. To explore early intervention strategies for HSCs activation and proliferation, miRNA profiles were sequenced from three patients with chronic hepatitis B-related hepatic fibrosis (HF). The miRNAs sequencing experiment and data analysis were conducted utilizing the Illumina HiSeq 4000 platform. In vitro, the proliferation and expansion capabilities of HSCs were detected using CCK8, EdU and colony formation assays. The examination of α-SMA, the indicator aHSCs, was performed through western blot assays. For in vivo investigation of the let-7g-5p/FGF5 axis, a bile duct ligation (BDL)-induced HF mice model was constructed and mmu-let-7g-5p agomir was delivered to mice via tail vein injection. Collagen deposition and the α-SMA level were assessed through histological staining including H&E, Masson, Van Gieson(VG), and immunohistochemical (IHC) staining. The miRNAs sequencing and bioinformatics analysis identified let-7g-5p as a promising anti-HF candidate. qRT-PCR and dual-luciferase reporter assays confirmed FGF5 as the direct target of let-7g-5p. let-7g-5p hampered the proliferation and expansion abilities of HSCs and decreased the α-SMA level by targeting FGF5 in vitro. In addition, H&E, Masson, VG and IHC staining demonstrated the let-7g-5p/FGF5 axis significantly mitigated collagen deposition and decreased α-SMA production in the BDL-induced HF mice. let-7g-5p suppressed the proliferation and expansion of HSCs and alleviated HF via targeting FGF5. The let-7g-5p/FGF5 axis could be an effective therapeutic target for reducing aHSCs abundance in HF.